Impact of operation duration on postoperative outcomes of minimally‐invasive right colectomy. (18th July 2022) - de'Angelis, Nicola; Schena, Carlo Alberto; Piccoli, Micaela; Casoni Pattacini, Gianmaria; Pecchini, Francesca; Winter, Des C.; O'Connell, Lauren; Carcoforo, Paolo; Urbani, Alessia; Aisoni, Filippo; Martínez‐Pérez, Aleix; Celentano, Valerio; et al.
Abstract: Aim: Operation time (OT) is a key operational factor influencing surgical outcomes. The present study aimed to analyse whether OT impacts on short‐term outcomes of minimally‐invasive right colectomies by assessing the role of surgical approach (robotic [RRC] or laparoscopic right colectomy [LRC]), and type of ileocolic anastomosis (i.e., intracorporal [IA] or extra‐corporal anastomosis [EA]). Methods: This was a retrospective analysis of the Minimally‐invasivE surgery for oncological Right ColectomY (MERCY) Study Group database, which included adult patients with nonmetastatic right colon adenocarcinoma operated on by oncological RRC or LRC between January 2014 and December 2020. Univariate and multivariate analyses were used. Results: The study sample was composed of 1549 patients who were divided into three groups according to the OT quartiles: (1) First quartile, <135 min ( n = 386); (2) Second and third quartiles, 135–199 min ( n = 731); and (3) Fourth quartile ≥200 min ( n = 432). The majority (62.7%) were LRC‐EA, followed by LRC‐IA (24.3%), RRC‐IA (11.1%), and RRC‐EA (1.9%). Independent predictors of an OT ≥ 200 min included male gender, age, obesity, diabetes, use of indocyanine green fluorescence, and IA confection. An OT ≥ 200 min was significantly associated with an increased risk of postoperative noninfective complications (AOR: 1.56; 95% CI: 1.15–2.13; p = 0.004), whereas the surgical approach and the type of anastomosis had no impact on postoperative morbidity. Conclusion: Prolonged OT is independently associated with increased odds of postoperative noninfective complications in oncological minimally‐invasive right colectomy.